2008
DOI: 10.1097/ccm.0b013e31817da674
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital advances in the management of severe penetrating trauma

Abstract: This article examines the most recent and salient advances that have occurred in battlefield prehospital care driven by our ongoing combat experience in the Iraq and Afghanistan and the evolution around the Tactical Combat Casualty Care concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 68 publications
1
23
0
2
Order By: Relevance
“…It is often used in combat to stop active bleeding by frontline medical providers. 20,21 The most important part of managing shock is simply to prevent it. 3,10Y13 Many graduates of the TCCC course and the special operations CUF course and combat lifesaver course have been able to make critical decisions on how to provide medical care in difficult circumstances but also have maintained the context of the greater mission requirements and tactical security.…”
Section: Teamworkmentioning
confidence: 99%
“…It is often used in combat to stop active bleeding by frontline medical providers. 20,21 The most important part of managing shock is simply to prevent it. 3,10Y13 Many graduates of the TCCC course and the special operations CUF course and combat lifesaver course have been able to make critical decisions on how to provide medical care in difficult circumstances but also have maintained the context of the greater mission requirements and tactical security.…”
Section: Teamworkmentioning
confidence: 99%
“…In military trauma these proportions are reversed. The panel felt that observations, clinical reports, policies, and practice patterns obtained in and relevant to the theater of war, while of potential benefit to civilian healthcare [63], should not be considered immediately transferrable to civilian trauma patients.…”
Section: Discussion and Panel Recommendationsmentioning
confidence: 99%
“…6,46,47 Current Committee on Tactical Combat Casualty Care guidelines recommend 500 mL of Hextend (Biotime Inc.), a synthetic colloid, because of the smaller weight and volume. 48 However, studies have not confirmed efficacy in shock and have documented risk including coagulopathies. [49][50][51][52] Hypertonic saline has also been studied because of the small volume and potential benefit for head trauma.…”
Section: Discussionmentioning
confidence: 99%